2008
DOI: 10.1186/1748-717x-3-15
|View full text |Cite
|
Sign up to set email alerts
|

High-dose intensity-modulated radiotherapy for prostate cancer using daily fiducial marker-based position verification: acute and late toxicity in 331 patients

Abstract: We evaluated the acute and late toxicity after high-dose intensity-modulated radiotherapy (IMRT) with fiducial marker-based position verification for prostate cancer. Between 2001 and 2004, 331 patients with prostate cancer received 76 Gy in 35 fractions using IMRT combined with fiducial marker-based position verification. The symptoms before treatment (pre-treatment) and weekly during treatment (acute toxicity) were scored using the Common Toxicity Criteria (CTC). The goal was to score late toxicity accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
58
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 28 publications
10
58
1
Order By: Relevance
“…According to published data, the majority of later rectal side effects manifest during a follow-up period of 36 months. 26,29 Nevertheless, these data compare well to those from the randomized trial published by Zietman et al, 29 which reported late grade 2 GI side effects in 17% of the patients and grade 3 reactions in 1% of the patients (total dose of 79.2 Gy). In addition, acute toxicity is predictive of late rectal and GU side effects.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…According to published data, the majority of later rectal side effects manifest during a follow-up period of 36 months. 26,29 Nevertheless, these data compare well to those from the randomized trial published by Zietman et al, 29 which reported late grade 2 GI side effects in 17% of the patients and grade 3 reactions in 1% of the patients (total dose of 79.2 Gy). In addition, acute toxicity is predictive of late rectal and GU side effects.…”
Section: Discussionsupporting
confidence: 84%
“…These results corresponded with published data. 4,9,25,26 The incidence of late grade ≥2 GI toxicity was 17% (IGRT) vs. 11% (non-IGRT), and only one patient suffered from rectal bleeding 12 months after treatment. There were no significant differences between treatment groups in regard to late grade ≥2 GU toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dynamic intensity-modulated radiotherapy (IMRT) using the sliding-window technique is currently applied for treatment in many clinical cases, particularly for patients with head-and-neck cancer or prostate cancer [1,3,7,15,16,19]. Dose distributions with improved conformity to the target can be obtained with this technique, leading to a reduced dose to the surrounding healthy tissue and critical organs [1].…”
Section: Introductionmentioning
confidence: 99%